2020
DOI: 10.21203/rs.3.rs-16034/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial DNA drives noncanonical inflammation activation via cGAS–STING signaling pathway in retinal microvascular endothelial cells

Abstract: Background Pathological stimuli cause mitochondrial damage and leakage of mitochondrial DNA (mtDNA) into the cytosol, as demonstrated in many cell types. The cytosolic mtDNA then drives the activation of noninfectious inflammation. Retinal microvascular endothelial cells (RMECs) play an important role in the inner endothelial blood–retinal barrier (BRB). RMEC dysfunction frequently occurs in posterior-segment eye diseases, causing loss of vision. In this study, we investigated the involvement of cytosolic mtD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We found that circ_0086296 inhibition mitigated proinflammatory cytokine generation in ox-LDL-treated HUVECs by reducing IFIT1 levels. IFIT1 could regulate the STAT1/STING/IRF-3 axis and STING can activate the downstream transcription factors including IRF3 and NF-κB [48][49][50]. Recent research has revealed that STING knockdown decreases atherosclerotic lesions and inflammatory factor expression in the aorta of atherosclerotic mice.…”
Section: Discussionmentioning
confidence: 99%
“…We found that circ_0086296 inhibition mitigated proinflammatory cytokine generation in ox-LDL-treated HUVECs by reducing IFIT1 levels. IFIT1 could regulate the STAT1/STING/IRF-3 axis and STING can activate the downstream transcription factors including IRF3 and NF-κB [48][49][50]. Recent research has revealed that STING knockdown decreases atherosclerotic lesions and inflammatory factor expression in the aorta of atherosclerotic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The cGAS-STING pathway is an immune response that recognizes cytosolic dsDNA, which can come from a variety of sources including the mitochondria [17][18][19]. Upon binding to dsDNA, cGAS (cyclic GMP-AMP synthase) dimerizes and becomes activated, whereupon it catalyzes the synthesis of cyclic dinucleotide cGAMP (2′3′ cyclic GMP-AMP) from ATP and GTP.…”
Section: Introductionmentioning
confidence: 99%